Development and Initial Validation of the Italian Mood Scale (ITAMS) for Use in Sport and Exercise Contexts - Quartiroli, Alessandro; Terry, Peter C.; Fogarty, Gerard J. (Frontiers in Psychology, 2017)
The current study presents initial validation statistics for the Italian Mood Scale (ITAMS), a culturally- and linguistically-validated Italian version of the Brunel Mood Scale (BRUMS: Terry & Lane, 2010). The ITAMS was administered to 950 sport participants (659 females), who ranged in age from 16 to 63 years (M = 25.03, SD = 7.62). In the first stage of the validation process, statistical procedures in Mplus were used to evaluate the measurement model. Multigroup exploratory structural equation modelling supported the hypothesized 6-factor measurement model for males and females separately and for the combined sample. Analysis of the scale scores using SPSS provided further support for the construct validity of the ITAMS with hypothesized relationships observed between ITAMS scores and measures of depression and affect. The development and validation of the ITAMS opens the way for mood-related research and sport or exercise interventions requiring mood assessments, in an Italian-language context.